Pakistan : Issues Related to the Government Securities Market and Government Debt Management - World Bank (Washington, DC, 2013)
The government of Pakistan borrows in the domestic market through a range of instruments, and this market is a critical source of funding for both shorter-term cash management and longer-term deficit-financing. The government has taken actions over the past 18 months that have enhanced the effectiveness of the market as a source of funding, as well as its efficiency. These include the movement toward more predictable, volume-based, market-determined pricing of government securities. Taking account of the dynamics of demand will be important as the government continues to develop its medium-term debt management strategy. Doing so will help identify potential constraints that may impede the implementation of the chosen strategy. Specific actions that the government is recommended to take include: a) reducing the number of tenors issued, b) consolidating the debt stock so as to improve liquidity in individual bonds, c) reducing time delays in auction processing, and d) developing and investor-relations function, with readily accessible information on the operation of the government securities market.